2017
DOI: 10.1016/j.aller.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference regarding atopy between children with familial Mediterranean fever and healthy controls?

Abstract: Children with FMF did not show an increase of atopic dermatitis, allergic rhinitis and asthma with respect to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Th17 cells are also one of the important components of allergic inflammation and asthma. This cell subpopulation is accepted as the major evidence of interaction between innate and adaptive immunity (14). Also, new researches on innate immunity and new signaling pathways show that they play a role in both autoinflammatory diseases and allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells are also one of the important components of allergic inflammation and asthma. This cell subpopulation is accepted as the major evidence of interaction between innate and adaptive immunity (14). Also, new researches on innate immunity and new signaling pathways show that they play a role in both autoinflammatory diseases and allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…rhinitis, and atopy rates were lower in the children with FMF compared to the normal population, FMF was found to be protective in terms of atopic sensitization and allergic rhinitis (13). Aydogmuş et al demonstrated that children with FMF had a non-significantly increased prevalence of atopic dermatitis (5.08%), allergic rhinitis (28.8%), and asthma (15.25%) compared to the control group, but atopy rates and mean eosinophil counts were similar (14). In a recent children study, Yildiz et al demonstrated that the prevalence figures of asthma, atopic dermatitis, and allergic rhinitis were 4.2%, 0.72%, and 0.87%, respectively, and asthma was more frequent in those without the exon 10 mutation.…”
Section: Conflict Of Interestmentioning
confidence: 97%
“…Genetic and environmental factors, as well as the design of study groups (children or adults), may have influenced the differences in the prevalence rate of atopy in autoimmune diseases. Another factor would be that some of those studies were based on the questionnaires (4)(5)(6)16). Epidemiologic studies were designed mostly on patients with SLE and RA (4,16).…”
Section: Discussionmentioning
confidence: 99%
“…Although, some studies reported the low prevalence of atopy in autoimmune diseases (4,5); the Th1/Th2 paradigm has been changed by the definition of Th17 and regulatory T (Treg) cells. Th17 play a role in the pathogenesis of both atopic and autoimmune diseases (6). Primary Sjögren's Syndrome (pSS) is a chronic autoimmune disease characterized by both organ-specific and systemic manifestations that primarily affects exocrine glands; especially the salivary and lacrimal, resulting in oral and ocular dryness due to lymphocyte infiltration and inflammation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Giảm nặng BCHTT bẩm sinh là một hội chứng suy giảm miễn dịch hiếm gặp có liên quan đến nhiều gen như: ELANE, HAX1, WAS, GFI1, G6PC3... [6], [8], [9]. Có hai phân nhóm chính của giảm nặng bạch cầu hạt trung tính bẩm sinh bao gồm: các đột biến gen trội nằm trên nhiễm sắc thể thường như đột biến gen ELANE (chiếm khoảng 40% -60% các trường hợp) và đột biến gen lặn trên nhiễm sắc thể thường như đột biến gen HAX1 (chiếm khoảng 30% các trường hợp).…”
Section: Bàn Luậnunclassified